Pendekatan Luar Ruang: Peningkatan Aktivitas dan Hasil Belajar Peserta Didik dalam Menulis Puisi di MTs Negeri 8 Kebumen - Asmini, Ami (Mulya Literasi Publishing, 2024)
This study aims to describe the activities, learning outcomes, and learning completeness of students in writing poetry with an outdoor learning approach at MTs Negeri 8 Kebumen. The researcher used the Classroom Action Research (PTK) method by covering the stages of planning, implementation, observation, and reflection. The subjects of this study were students of class VIII G, totaling 32 people. Data were collected through test and non-test techniques. Data presentation was done with informal techniques. The results showed that there was an increase in student learning activities from 72.97% to 80.94%, and there was also an increase in student learning outcomes from 65.23% to 81.45%. This means that the increase in learning outcomes in poetry writing activities with an outdoor approach is 16.22%. In cycle, I, 21 students completed their learning with a percentage of 65.63%, and increased in cycle II to 28 people with a percentage of 87.50%.